Geotechnical sustainability in the United Arab Emirates - Current status and opportunities - Sochanik, Ryan (International Journal of Engineering and Technology, 2020)
The United Arab Emirates (UAE) has aligned its development polices and agendas with the United Nationâ€™s Sustainable Development Goals, a driver provided by the UN to contribute towards sustainability. As part of this commitment, sustainability in the construction industry is continually evolving. The movement towards sustainability in construction is challenging in the UAE due to the climate, geographical location, economy and availability of natural resources. The UAE has therefore developed specific legislation requiring â€œgreen constructionâ€. Over and above the legislation, developers in the UAE recognise the value in achieving certified â€œgreenâ€ credentials through the adoption of optional sustainability assessments in their projects. Geotechnical engineering is a specific branch of civil engineering focussing on soil-structure interaction and geotechnical input is required for the design and construction of almost every civil engineering project. This study reviews the current mandatory regulations and practices, with respect to the input from geotechnical engineering. It highlights that as a discipline there is little contribution towards sustainability and concludes that geotechnical engineering can and needs to contribute more. Practical solutions to improve geotechnical engineering sustainability are proposed, as are opportunities for further research and development of geotechnical engineering sustainability.Â Â